HUBUNGAN ANTARA SELF EFFICACYDAN DUKUNGAN SOSIAL ORANGTUA DENGAN SELF REGULATED LEARNING SERTA IMPLIKASINYA TERHADAP BIMBINGAN DAN KONSELING - Ade Chita Putri Harahap Neviyarni S Daharnis (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This research was based on how important to increase the students self regulated learning. Self efficacy and parent social support were the factors assumed to affect the self regulated learning. The purpose of this research were to describe: (1) self efficacy, (2) parent social support, (3) self regulated learning, (4) the relationship between self efficacy with self regulated learning, (5) the relationship between parent social support with self regulated learning, and (6) the simultaneous relationship between self efficacy and parent social support with self regulated learning. This research used a quantitative method with correlative descriptive type. The population in this research was the students at SMP Negeri 29 Padang many as 522 students. The sample in this research was many as 213 students who selected with a proportional stratified random sampling technique. The instrument was a Likert scale model. The results of instrument reliability test showed that self efficacy was much as 0.851, parent social support 0.946 and self regulated learning 0.860. The data were analyzed by using descriptive statistic, simple regression, and multiple regression. This discover research show: (1) students self efficacy was at high category, (2) students parent social support was at high category, (3) students self regulated learning was at high category, (4) there was a positive and significant relationship between of self efficacy to self regulated learning, (5) there wasa positive and significant relationship between of parent social support to self regulated learning, and (6) there wasa positive and significant simultaneous relationship between of self efficacy and parent social support with self regulated learning. Implications of these results could be used as suggestion to arrange programs of guidance and counseling service at the school.